2015
DOI: 10.2217/nnm.15.183
|View full text |Cite
|
Sign up to set email alerts
|

EGCG/Gelatin-Doxorubicin Gold Nanoparticles Enhance Therapeutic efficacy of Doxorubicin for Prostate Cancer Treatment

Abstract: Laminin 67R receptor-mediated delivery of DOX using the AuNPs enhanced cellular uptake of DOX and improved apoptosis of PC-3 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…EGCG and gelatin-doxorubicin conjugate (GLT-DOX)-coated gold nanoparticles (DOX-GLT/EGCG AuNPs) were produced to improve specific uptake of doxorubicin in PC3 cells using EGCG/67-LR receptor-mediated delivery. Apoptosis of DOX-GLT/EGCG AuNPs treated PC3 was improved in comparison with cells treated with DOX [165].…”
Section: Nanotechnology Strategies To Improve Gtcs Bioactivitymentioning
confidence: 89%
“…EGCG and gelatin-doxorubicin conjugate (GLT-DOX)-coated gold nanoparticles (DOX-GLT/EGCG AuNPs) were produced to improve specific uptake of doxorubicin in PC3 cells using EGCG/67-LR receptor-mediated delivery. Apoptosis of DOX-GLT/EGCG AuNPs treated PC3 was improved in comparison with cells treated with DOX [165].…”
Section: Nanotechnology Strategies To Improve Gtcs Bioactivitymentioning
confidence: 89%
“…In addition, because DOX has the fluorophore feature, it is easily detected and quantitated; therefore, it has been extensively applied in many studies of tumor treatment using drug carriers, such as gold particles, magnetic particles, and microbubbles. 15,16 Some researchers have reported that pure low-frequency US could promote the uptake and distribution of liposomal DOX in prostate cancer xenografts, which might be associated with the production of cavitation nuclei by fluid in xenografts, such as blood under US excitation. 17 Since Gramiak et al first discovered that microbubbles could enhance US images in 1968, UCAs have received extensive attention.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gold nanoparticles (AuNPs) have attracted much attention in the field of biomedical imaging and clinical diagnostics, in the last decade [45,46]. These NPs can also be surface modified by attaching targeting ligands and tagged with imaging molecules for specificity and effectiveness of the cancer diagnosis and therapeutics [39].…”
Section: Cytotoxic Assay Pc3 Cellsmentioning
confidence: 99%